A biomimetic phenol substituent effect on the reaction of a dimethylplatinum(ii) complex with oxygen: proton coupled electron transfer and multiple proton relay1. Issue 51 (28th June 2015) - Moustafa, Mohamed E.; Boyle, Paul D.; Puddephatt, Richard J.
<x xml:space="preserve">Abstract</x> A phenol substituent has a dramatic effect on the oxidation of a dimethylplatinum(ii) complex with O2.